Morphology and growth of plantain and banana: IITA research guide, No. 66 - Swennen, Rony L.; Ortíz, R. (1997)
Plantain and banana (Musa s pp.J are giant perennial herbs which originated in Southeast Asia. Musa is an important food crop in the humid forest and mid-altitude ecologies of sub-Saharan Africa. Several criteria are used to distinguish the different types of cultivated plantain and banana, evolved from M . acu-minata and M. balbisiana. The corm is the real stem of the Musa plant and produces 10-15 buds, which may develop into branches called suckers. Suckers are used as planting material. Foliage leaves form the pseudostem, which supports the inflorescence the inflorescence may be complete or incomplete, depending on whether it includes all or only parts of a Musa inflorescence: female flowers, neutral flowers, and male bud. Fruit development includes the maturation and ripening periods.